Pharmacokinetics of Isepamicin during Continuous Venovenous Hemodiafiltration - Breilh, Dominique (American Society for Microbiology, 1999)
The objective of this study was to analyze the pharmacokinetics of isepamicin during continuous venovenous hemodiafiltration. Six patients received 15 mg of isepamicin per kg of body weight. The mean isepamicin concentration peak in serum was 62.88 ± 18.20 mg/liter 0.5 h after the infusion. The elimination half-life was 7.91 ± 0.83 h. The mean total body clearance was 1.75 ± 0.28 liters/h, and dialysate outlet (DO) clearance was 2.76 ± 0.59 liters/h. The mean volume of distribution was 19.83 ± 2.95 liters. The elimination half-life, DO clearance, and volume of distribution were almost constant. In this group of patients, the initial dosage of 15 mg/kg appeared to be adequate, but the dosage interval should be determined by monitoring residual isepamicin concentrations in plasma.